The correlation between dip width and peak flux in Cir X-1 - Yu, Zhuo-Li; Zhang, Shu; Zhang, Shuang-Nan; Li, Xiang-Dong; Chen, Yu-Peng; Peng, Jing-Qiang; Shui, Qing-Cang; Yan, Zhe; Kong, Ling-Da; Wang, Peng-Ju (Astronomy and astrophysics (Berlin), 2024)
In this work we analyzed the long-term X-ray variation of Cir X-1 and its NICER spectra. The dip width and the peak flux after periastron are obtained. Our findings show a negative correlation between the dip width and the peak flux. A new scenario is introduced to explain the correlation. The disk height is higher at a larger radius in the standard model. When the neutron star (NS) moves away from periastron, the contraction of the equipotential surface causes the height of the outer disk to increase significantly. It blocks the X-ray emission near the NS. Subsequently, the height of the outer disk gradually decreases due to the viscosity. The viscous timescale is inversely proportional to the height of the disk, and the height of the outer disk is proportional to the mass transferred from the companion near periastron, thus the peak flux. Consequently, the duration of the obscuring, corresponding to the dip width, is inversely proportional to the peak flux. Moreover, we introduce a new ephemeris MJD( N ) = 43075.0 + 16.5843 N − 4.778 × 10 −5 N 2 based on the dip-in phases (ingress phase of the dip).